Efficient Road Traffic Management using Fuzzy and Genetic Approaches - Vinay Yadav, Dr. Jitesh P. Tripathi, Dr.Bhawesh Kumar Thakur (Design Engineering, 2021)
In this Paper, we discussed about a mathematical model of cross road traffic management issues. In the existing methods, the linear models which are inflexible in principle, the proposed methodology will meet the sequential variations occurs in the means of non-cyclic method which aim at taking decisions as per the current traffic situation on a moment. The response time of decision taking is short and by the consequence of waiting time period of vehicles are reduced. The implementation of the fuzzy and genetic algorithm in this paper proves the accuracy and efficiency in the parameterizing the each of those variables by playing a crucial role in the efficient management of traffic crossroad management. As per the implementation, we focused on the other heuristics to improve the results with the help of other additional constraints.